Penguatan Pemasaran Online, Inovasi Produk, dan Penerapan Akuntansi Sederhana pada Bisnis Kuliner Depot Ceria Gresik - Mustika Winedar; Maria Agustini; Sri Utami Ady; Wahyu Widayati (STIE Malangkucecwara, 2022)
Empowerment of women entrepreneurs by opening access to business, encouraging increased digital capabilities and creating a fair and safe work environment is a global issue in order to reduce inequality in women's equality in the economic field. As part of the global community, this community service program aims to provide solutions to the problems faced by Ceria entrepreneurs, namely problems in product, marketing, and financial aspects. The short-term solution offered to overcome the problems above is the first to create product innovation. Second, optimize online marketing. And third, increasing knowledge and application of simple accounting for MSME businesses. Transfer of knowledge and skills is carried out using training and mentoring methods. And the results of this community service activity are the creation of innovative products in the form of Sushi Krawu, the use of social media Tik Tok, Instagram and the Go-food and Grab-food delivery order applications and the preparation of balance sheet and income statement. The implications of the implementation of this community service program are an increase in the variety of culinary products offered through the interaction of business actors with customers on social media and the integration of online sales applications into levers to increase sales, increase financial accountability, and professionalism so as to create economic independence and increase empowerment for entrepreneurs woman.